The molecular phylogeny of Omalisidae (Coleoptera) defines the family limits and demonstrates low dispersal propensity and ancient vicariance patterns. (5th October 2017) - BOCEK, MATEJ; FANCELLO, LUCA; MOTYKA, MICHAL; BOCAKOVA, MILADA; BOCAK, LADISLAV
Abstract: The genus‐level molecular phylogeny of Omalisidae Lacordaire is presented for six of seven currently recognised genera. The monophyly and internal relationships are well‐supported including the taxa which were placed in other elateroid families. We conducted molecular analyses using maximum‐likelihood optimality criterion and Bayesian inference and 18S, 28S rRNA, rrnL and cox1 mtDNA markers (4038 homologous positions). Euanoma Reitter is a sister lineage to other Omalisidae. Thilmanus Gemminger is related to Paradrilus Kiesenwetter and Phaeopterus Costa. Thilmaninae Kazantsev (erected in Lycidae), Euanomini Kazantsev (erected in Drilidae), and Paradrilinae Kundrata et al . are removed from within omalisid classification due to widely overlapping concepts of generic and subfamilial taxa. Pseudeuanoma Pic, syn.n. was recovered as a paraphylum and is a younger synonym of Euanoma . Euanoma caligo (Kazantsev), comb.n., E. ionica (Pic), comb.n., E. obscura (Pic), comb.n. and E. reitteri (Pic), comb.n. are newly combined with Euanoma . The earlier classification of incompletely metamorphosed taxa was affected by the parallel evolution of morphological traits. We report on the discovery of the incompletely metamorphosed female of Thilmanus obscurus Baudi and compare it with the female of O. fontisbellaquei Geoffroy. The female is weakly sclerotised, has physogastric abdomen, vestigial elytra, no wings and simplified thoracic morphology. Furthermore, we describe allopatric ranges of ancient omalisid lineages and vicariance events resulting from geological transformations in the Mediterranean. Euanoma was split from other Omalisidae in the late Jurassic and remains restricted to the Eastern Mediterranean. Omalisus Geoffroy split from the Iberian genera in the Cretaceous and most species occur on southern slopes of the Alps and in the western Balkan. The separation of Paradrilus and Thilmanus + Phaeopterus corresponds with the isolation of the Ebro and Hesperian massifs in the Cretaceous; the fauna of Sardinia and Corsica is of Iberian origin and Phaeopterus dispersed from these islands to the Elba and Apennine Peninsula. The diversity of Omalisidae has an ancient origin, but survived till present only in the Mediterranean, mostly in Pleistocene refugia close to the sea. Abstract : We report on the discovery of the incompletely metamorphosed female of Thilmanus obscurus . We present a molecular phylogenetic analyses of the beetle family Omalisidae, date the origin of genera and analyze the extant distribution of the family. Omalisidae are the ancient group of beetles occurring in the Mediterranean hotspot and they are mostly limited to coastal glacial refugia.